Covid-19 Prevention Zonation with Geographic Information System Based on Health Protocols in Southeast Sulawesi - Arum Dian Pratiwi; Wahyu Ishaq Trisnandi; Fifi Nirmala (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2022)
Efforts to prevent COVID-19 in Indonesia include the 3M movement. This movement is a COVID- 19 Task Force campaign to do 3M (Using masks, washing hands, and maintaining a safe distance) in preventing COVID-19. In relation to health protocols, it is necessary to review a person's desire to carry out or not carry out these preventive measures, this can be reviewed in the Health Belief Model theory. During the COVID-19 pandemic, the public often obtains information based on geographic information systems regarding the zoning of the development of COVID-19 in each region. Geographic Information System is the best medium for monitoring by mapping because it has a very good ability to visualize spatial data and its attributes. The purpose of this study is to find out the zoning of COVID-19 prevention in the 3M movement based on the Geographic Information System in the people of Southeast Sulawesi in 2020. This study uses a quantitative descriptive type of research. There is 17 districts/cities, there is no red zone on the variables of vulnerability, seriousness, benefits, barriers, health motivation, and cues to act, and only 1 region has good compliance (green zone) in prevention of COVID-19 through the 3M movement. An in- depth study of the variables studied with a more detailed methodology is needed so that the results obtained can complement each other to develope of science.